Carrots and Sticks : The Political Economy of Nutrition Policy Reforms - Natalicchio, Marcela; Garrett, James; Mulder-Sibanda, Menno; Ndegwa, Steve; Voorbraak, Doris (World Bank, Washington, DC, 2013)
The World Bank and other development partners have been involved in the implementation of nutrition programs for over 30 years. While a number of these programs have become successful and sustainable large-scale operations, many others have been hindered by political and administrative obstacles. The disparate results of these nutrition programs suggest that generating technically sound knowledge about nutrition and providing it to policymakers is not enough to ensure good results. It is also crucial to understand the political context, and the constraints and motivations of politicians, public officials, and other relevant players to initiate, implement, and sustain sound policies. In May 2007 the World Bank held an international workshop on these issues to help increase the impact of nutrition programs and policies at the country level. This paper summarizes the results of that workshop. Drawing from the political economy literature, it presents two frameworks for understanding how to undertake action to put nutrition on the agenda and move it forward, as well as insights on how and why political factors derail reforms and how to keep that from happening. These frameworks are accompanied by a discussion of the politics of nutrition policies, including typical obstacles to policy development and implementation, and possible solutions. To complement the political economy approach, the paper also draws on the insights that management and organizational fields offer regarding change promotion. Experiences from Senegal, Madagascar, Ghana, Tanzania, Benin, and India are discussed, sketching out the history of nutrition policies and the factors that promoted change, main obstacles and challenges. The paper closes with an attempt to encapsulate all elements presented in a single analytical framework, and provides plans of action for specific countries as prepared by some of the participants.